Weight underestimation linked to anxiety and depression in a cross-sectional study of overweight individuals in a Sami and non-Sami Norwegian population: the SAMINOR Study - Kirsti Kvaløy; Marita Melhus; Ann Ragnhild Broderstad; Anne Silviken (BMJ Open, 2019)
Objectives Underestimation of overweight/obesity may prevent weight loss attempts, resulting in further weight gain and maintenance of overweight. Mental health benefits may nevertheless surpass negative consequences. Our main objective was to study the association between underestimation of overweight/obesity and symptoms of anxiety and depression in Sami and non-Sami populations.Design Population-based cross-sectional study.Setting The SAMINOR 2 Clinical Study with participants from 10 municipalities in Northern Norway enrolled between 2012 and 2014.Participants The study included 3266 adults of multiethnic rural origin with overweight/obesity (body mass index (BMI) ≥25 kg/m2) whereof 1384 underestimated their weight (42%).Primary and secondary outcome measures Primary outcome measure was symptoms of anxiety and depression and secondary outcome measures were BMI and the demographic variables: sex, age, education and marital status.Results A higher proportion of Sami men compared with non-Sami men were obese, and reported more symptoms of anxiety and depression. More men than women, and a higher proportion of Sami women compared with non-Sami women, underestimated their weight. Multivariable-adjusted analyses showed that women were less likely to underestimate their weight compared with men (OR 0.43, 95% CI 0.33 to 0.55 in Sami and OR 0.33, 95% CI 0.26 to 0.42 in non-Sami), higher BMI was protective against weight underestimation (OR 0.72, 95% CI 0.69 to 0.75 in Sami and OR 0.63, 95% CI 0.60 to 0.67 in non-Sami), slightly higher odds of weight underestimation were observed with increasing age in both ethnic groups (OR 1.03, 95% CI 1.01 to 1.05 in Sami and OR 1.02, 95% CI 1.00 to 1.03 in non-Sami), while higher education lowered the odds in non-Sami (OR 0.69, 95% CI 0.55 to 0.87). Weight underestimation was protectively associated with anxiety and depression in Sami men (OR 0.48, 95% CI 0.27 to 0.84) and in non-Sami women (OR 0.44, 95% CI 0.25 to 0.78) adjusted for age, BMI, education and marital status.Conclusions Independent of ethnicity, more men than women underestimated their weight. Underestimation of weight was protectively associated with anxiety and depression in Sami men and non-Sami women.